Challenges of Nepalese Women in Parliamentary Elections - Acharya, Indu (Tribhuvan University Journal, 2013)
The country has just passed from the 2nd election for the constituent assembly. Assuring the minimum level of women in the house has been a real challenge; however the recent CA election results have shown a clear decline in the presence of women lawmakers in the house. Despite hard struggle and pressure of women activists and civil society the political parties of the country have failed to keep the level of women’s presence in the CA to a level of 33% as like in the previous CA. In this paper, the researcher has examined the issues and challenges related to women’s access to the legislatives in the country in general based on the comparative overview of the last two CA elections from the perspective of women’s participation.